Betulinic acid protects against ovarian impairment by decreasing F-2 toxin-induced oxidative stress and inflammation associated with the downregulation of p38 expression in mice - Li Kong; Xinyu Gao; Lijuan Zhu; Xing Lin; You Huang; Chunlin Huang; Wenjiang Yang; Yazhi Chen; Haoqiang Zhao; Jing Wu; Zhihang Yuan; Jin’e Yi (Food Science and Human Wellness)
F-2 toxin is an estrogenic mycotoxin that causes reproductive disorders in animals. Betulinic acid (BA) is a natural pentacyclic lupane-structure triterpenoid that has diverse pharmacological activities. In this study, the antioxidative and anti-inflammatory effects of BA and its underlying mechanism are explored in F-2 toxin-triggered mouse ovarian damage. We found that BA alleviated the F-2 toxin-induced ovarian impairment by stimulating follicle growth, reducing inflammatory cell infiltration, repairing damaged mitochondria and endoplasmic reticulum. Simultaneously, BA not only reversed F-2 toxin-induced reduction of follicle stimulating hormone (FSH) and luteinizing hormone (LH) levels in the serum, but also restrained the protein expression of the estrogen receptors α (ERα) and ERβ. Moreover, BA restored the balance of F-2 toxin-induced ovarian redox system disorders. Subsequently, we found that 0.25 mg/kg BA played an anti-inflammatory role in the F-2 toxin-induced ovarian impairment by decreasing interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) mRNA expression, as well as inhibiting p38 protein expression.These data demonstrated that BA exerts its protective effect on F-2 toxin-induced ovarian oxidative impairment and inflammation by inhibiting p38 expression, which implies a natural product-based medicine to ameliorate F-2 toxin-caused female reproductive toxicity and provides a detoxifying method for food contaminated by mycotoxin.